The Emily Post book of etiquette for young people - Post, Elizabeth L.; Post, Emily 1873-1960. (New York Funk & Wagnalls, 1967)
Covers questions of behavior at home and in public, discussing personal appearance, conversation, correspondence, everyday manners, dating, travel, tipping, and parties.
Keywords: Etiquette for children and teenagers; Etiquette